EFEKTIVITAS PELAKSANAAN E-PROCUREMENT DALAM MENDUKUNG GOOD GOVERNANCE - Suhendri, Sujianto, Meyzi Heriyanto (JIANA ( Jurnal Ilmu Administrasi Negara ), 2019)
Effectiveness of the Implementation of E-Procurement in Supporting Good Governance. The purpose of this study was to determine the effectiveness of the implementation of eprocurement in supporting good governance in Riau Province. This study uses qualitative research methods with descriptive data analysis. In data collection researchers used interview, observation, and documentation techniques. By using key informants as sources of information and data analysis with triangulation techniques as sources in testing the validity of data. The results of this study by using an e-procurement program in the procurement of goods and services within the Riau provincial government have been carried out very effectively compared to the conventional system for the perpetrators of auction services.